Health Psychology in Practice - Abraham Charles; Michie Suzan (Bps Blackwell, 2004)
This book provides a comprehensive overview of the competences required for professional training in the UK (BPS Stage 2 Qualification in Health Psychology). Foreword, Acknowledgements, Health Psychology in Practice: Introduction, Health Psychology Training: The UK Model, International Commentaries, Using Theory in Research, Planning Research: Design and Sample and Measures, Analysing and Reporting Data in Health Research, Designing and Conducting Qualitative Studies, Planning and Conducting Systematic Reviews, Writing Grant Applications, Writing for Publication, Using Theory in Psychological Interventions, Consultancy: What Is It and How Do You Do it and Does it Make any Difference?, Health Psychology within Organizational Contents, Changing Behaviour to Improve Health, Studying and Changing Healthcare Professionals' Behaviour, Training and Teaching, Developing and Evaluating Training and Teaching, Supervising Effectively, Professional Roles and Practice, Health Psychology within Health Service Settings, A Framework for Professional Practice, Author and Subject Index.